Cytotoxic indole alkaloids and polyketides produced by a marine-derived fungus Aspergillus flavipes DS720 - Xu, An; Xu, Xiang-Nan; Zhang, Mi; Li, Chun-Lian; Liu, Li; Fu, De-Yuan (Frontiers in Microbiology, 2022)
Marine-derived microorganisms possess unique metabolic pathways to produce structurally novel secondary metabolites with potent biological activities. In this study, bioactivity-guided isolation of the marine deep-sea-derived fungus Aspergillus flavipes DS720 led to the characterization of four indole alkaloids (compounds 1−4) and four polyketides (compounds 5−8), including two new indoles, flaviloids A (1) and B (2) with a C-6 reversed prenylation, and a new azaphilone, flaviazaphilone A (5). Their chemical structures were unambiguously established by extensive interpretation of spectroscopic data, including 1D/2D NMR and HRESIMS data. The absolute configuration of the new compound 5 was solved by comparing the experimental and calculated ECD spectra. Since sufficient amount of flaviloid A (1) was obtained, 1 was subjected to a large-scale cytotoxic activity screening against 20 different human tumor cell lines. The results revealed that 1 showed broad-spectrum cytotoxicities against HeLa, 5637, CAL-62, PATU8988T, A-375, and A-673 cell lines, with the inhibition rates of more than 90%. This study indicated that the newly-discovered indole alkaloid 1 may possess certain potential for the development of lead compounds in the future.